Notary Responsibility For Development And Registration Of Fidusia Warranties On Line Against Fidusian Recipients In Demak District - Widayat Aris Prasetiyo (Sultan Agung Notary Law Review, 2020)
The implementation of making and registering an online Fiduciary Guarantee Deed in Demak Regency, the Notary must carry it out on his own without being represented by the employee, because the Notary must know for sure about the correctness and data input. Based on this, this research discusses the Notary's responsibility, the obstacles in fulfilling the Notary's responsibility, and efforts to overcome the obstacles in fulfilling the Notary's responsibility for the making and registration of the Fiduciary Guarantee Deed Online for Fiduciary Recipients (Creditor) in Demak Regency. Types / types of empirical juridical research, analytical descriptive specifications, data collection methods include primary legal materials and secondary legal materials, qualitative analysis methods. The responsibility of the Notary, starting from the making of the Fiduciary Guarantee Deed including the supporting documents in the making of the Fiduciary Security Deed, up to the implementation of data input in the context of implementing the Fiduciary Guarantee Deed registration is the full responsibility of the Notary concerned. The obstacles are: First, the internal factor is that there is an error in data input made by a relevant Notary regarding the procedures and procedures for making an Authentic Deed. Second, external factors related to the Credit Approval Memorandum (CAM) of the Fiduciary, Efforts to overcome obstacles, namely: First, obstacles from the online operational system, so if the data has been sent, the Fiduciary Certificate has not been printed online. Second, in terms of application an error occurs, then you can send an email requesting corrections and corrections to the email address. Third, in terms of data storage in the system, the notary will first perform manual recording. Fourth, in terms of the appearance of the statement letter and the Fiduciary Guarantee Certificate, the Notary will re-enter the data that is not completely printed. Fifth, in terms of signatures, the notary will report the imperfect printing of the system.